Pervasive Computing 10th International Conference, Pervasive 2012, Newcastle, UK, June 18-22, 2012. Proceedings - Kay, Judy.; Lukowicz, Paul.; Tokuda, Hideyuki; Olivier, Patrick; Krüger, Antonio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 10th International Conference on Pervasive Computing, Pervasive 2012, held in Newcastle, UK, in June 2012. The 28 revised papers presented were carefully reviewed and selected from 138 submissions. The contributions are grouped into the following topical sections: activity capturing; urban mobility and computing; home and energy; HCI; development tools and devices; indoor location and positioning; social computing and games; privacy; public displays and services.
Keywords: Application software; User interfaces (Computer systems).; Computer communication systems; Computer security; Computer simulation; Computers and civilization; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Computer Communication Networks; Systems and Data Security; Simulation and Modeling; Computers and Society